SHIYASAH THOUGHT: AMAR MA’RUF NAHI MUNKAR ACCORDING TO AL-MAWARDI - Febriyani, Fifi Nur Lynda; Jinan, Mutohharun (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research aims to enhance our understanding of Muslim figures with political ideologies, examined through the concept of hisbah "Amar ma'ruf nahi munkar" (enjoining what is right and forbidding what is wrong). The research employs a library research approach, drawing on both primary and secondary data sources. Primary data is collected through translations of Ahkam As-Sulthaniyah, while secondary data consists of writings on the political ideologies of other Muslim figures and related political thought. Through a thorough and authoritative literature review, it is found that governments have a vested interest in ensuring social justice and morality within society through governmental oversight institutions. Al-Mawardi is a highly regarded Muslim scholar known for his political ideologies, predating Western recognition of such ideologies. Hence, it is compelling to examine his political concepts within the framework of "Amar ma'ruf nahi munkar".